FACTORS INFLUENCING FIRST-YEAR STUDENTS’ INTENTION TO STAY - Deacon, Elmari; Viljoen, Corrie (South African Journal of Higher Education, 2016)
The aim of this study was to identify whether social support, academic fit, the psychological conditions of meaningfulness and availability and engagement can predict first-year students’ intention to stay in an educational environment. A quantitative, cross-sectional design was used to achieve the specific research objectives, making use of a convenience sample (n = 304). The measuring instruments were based on the Multidimensional Scale of Perceived Social Support, the Psychological Conditions Scale, the Academic Fit Scale, the Work Engagement Scale, and the Intention to Leave Scale. The results indicated that social support had direct and indirect effects (via academic fit) on intention to stay, as did academic fit, the psychological conditions of availability and meaningfulness and engagement. The findings of this study emphasise the importance of helping students at fitting into the academic environment, choosing the right career, and receiving sufficient social support to ensure that they stay on at an academic institution and complete their studies.